(untitled) - Varcarolis, Elizabeth M. (St. Louis, 2004)
This handy pocket guide is designed to assist in the assessment of psychiatric nursing clients, the formulation of nursing diagnoses, and the design of psychiatric nursing care plans. The book contains practical, clinically oriented information students can carry with them as they visit the inpatient unit, community mental health setting, or home care setting. It is also an excellent resource for the new graduate and/or practicing nurse
Keywords: Psychiatric nursing,Chăm sóc tinh thần